Paradise Lost. From Eutopia to Atopia - Ugo Rossi (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
At the origin of every architectural and city project, there is a nostalgia for Paradise or the aspiration to build this wonderful place we have lost. Visions, architecture and city projects are necessarily prophetic images in search of a happy life on Earth. Every proposal for the city, every project, and every plan is a Utopia, an ideal place which aspires to become Eutopia. However, given the many visions and proposals, we can ask ourselves whether these Utopias have fulfilled their promise to achieve a good place or are dystopias. In light of this unknown factor, this paper intends to reflect on some visions and proposals of the city. Some of them constitute the foundations of urban planning – like Howar’s Garden City, Wright’s Broadacre City, Le Corbusier’s Radiant City, the functional city of CIAM – others, elaborated by Erwin Anton Gutkind, Iannis Xenakis, Constantinos Doxiadis, Takis Zenetos, originated from different assumptions, deluding themselves that they are solving the problems of the contemporary city or represent its last frontier, such as the Smart City.